The outcome of pleomorphic sarcoma at University Malaya Medical center - a fifteen - year review - Chan, C.Y.W.; Janarthan, N.; Vivek, A.S.; Ortho, M.S.; Jayalakshmi, P. (Malaysian Medical Association, 2008)
Pleomorphic sarcoma is the most common sarcoma. Reports of outcome as well as evaluation of prognostic factors in the literature show great variation. We looked at our experience in treating this tumour at University Malaya Medical Center. This is a review of patients diagnosed with Pleomorphic Sarcoma from January 1990 to December 2005 at University Malaya Medical Center. Outcome measures studied are the overall survival, disease free survival and local recurrence of disease. Prognostic factors for survival and local recurrence which were studied are the tumour size, depth, stage, type of surgery, adjuvant therapy, and surgical margin. There were fifty four patients available for analysis of demographics. The mean age at presentation was 52.3 +/- 16.7 years. There were thirty male patients (56) and twenty four female patients (44) in the study population. The patients were predominantly Malay (44.4) and Chinese (42.6). There were two Indian patients (3.7) and five patients from other races (9.3). Thirty patients had disease affecting the extremities while six patients had disease affecting the trunk. Patients with tumour affecting the trunk had 100 mortality. In patients with tumour affecting the extremity, 46.7 presented with Stage 3 disease. The overall median survival was 39 months. The overall survival rate at 3 years was 53.3 and the 5 years was 30.0. The disease free survival rate at five years was 27.6. However, if patients who presented with metastasis were excluded, the 5 year survival rate was 60 while the disease free survival was 53.3. Recurrence rate was 33.3. Factors affecting survival was stage, size and location of tumour. No factors were found to correlate with higher local recurrence rate. In conclusion, Pleomorphic Sarcoma is a heterogenous disease with variable outcome. In our centre, late presentation with advanced disease significantly affects the overall outcome of this condition. Tumour size and location are important prognostic factors. Inherent tumour behavior and aggressiveness probably outweigh current treatment modalities as the most important prognostic factor in the management of Pleomorphic Sarcoma.